Evaluation of Reliability-based Fatigue Strain Data Analysis for an Automobile Suspension Under Various Road Condition - Mohamad Nasir, Nadia Nurnajihah; Abdullah, Shahrum; Karam Singh, Salvinder Singh; Mohamed Haris, Sallehudin (International Journal of Integrated Engineering, 2018)
This work aimed to analyse fatigue-based reliability for automobile suspension on the basis of the strain load signal from an automobile under operating conditions. Fatigue life was used to ensure the aging of the component, and it was suitable for use for longer than the standard age given. The damage behaviour patterns for each retained edited signal from 100% to 85% were used to predict the fatigue durability of the suspension with a sampling frequency of 500 Hz for various road conditions. The extended global statistics were computed to determine the behaviour of the signal. Accelerated durability analysis was used to remove the low-amplitude cycles, which contributed minimally toward the total damage, by considering the effects of mean stresses. The reliability assessment, hazard rate function and mean time-to-failure (MTTF) based on the retention signal were predicted through fatigue strain data analysis. Changes were observed from a range of below 15% and above 60% of the length of the actual original signals due to the low amplitude. Extended global statistics showed scale parameter of 75 and 94 with an MTTF of 1.25Ã—103 and 1.27Ã—103 cycles. The retention signal loads provide an accurate signal editing technique for predicting fatigue life with good reliability characteristic understanding for the suspension part.